Amplitude e sobreposição do nicho ecológico de Euglossa cordata e Eulaema nigrita (Hymenoptera, Apidae, Euglossini) - Lima, Irailde do Nascimento (2017)
This study was deseloped at four ranches of the urban area of the municipal district of São Carlos – São Paulo, Brazil, in the period of November of 2005 to January of 2007, analyzing pollen loads of females of Euglossa cordata and Eulaema nigrita that have visited flowers of Thevetia peruviana (Apocynaceae) in the streets of the city, and shown points of coccurence of those bees in the Neotropical Region. The objective was to evaluate the overlap of trophic niches for the immatures in collection places and the amplitude of ecological niches between the two species of bees. Qualitative and quantitative analyses were accomplished on 175 pollen load samples for Euglossa cordata and 45 for Eulaema nigrita collected at the four ranches of the urban area, and made modeling the ecological niche starting from the construction maps of potential distribution for the two species of bees and and species of more abundant plants species in their diets. The analysis showed 37 pollen types used in the diet of Euglossa cordata and 12 for Eulaema nigrita, where the species of more abundant plant in the diet of both bees were Psidium guajava L. (Myrtaceae), Tradescantia zebrina Heynh. ex Bosse (Commelinaceae) and Solanum paniculatum L. (Solanaceae). The types more frequent pollen in the diet toEulaema nigrita were of Solanum paniculatum and Psidium guajava, while Euglossa cordatacollected Solanum paniculatum and Tradescantia zebrina, being Solanum paniculatum the plant species shared by both species of bee. The modeling of potential distribution, for Euglossa cordataand Eulaema nigritashowed that both evince potential distribution similar in areas of occurrence in the Neotropical region, and they overlap in the distribution of ecological niche in most areas of occurrence in the region.